Quantitative electroencephalography characteristics in delirium with various etiologies: A multicenter study - Julia van der A; Robert Fleischmann; Annerose Mengel; Lisette Vernooij; Cornelis Stam; Sophie Leroy; Pauline Schneider; Johannes Ehler; Arjen Slooter; Edwin van Dellen (NeuroImage: Clinical)
Aim: Delirium is a manifestation of acute encephalopathy, which has a heterogeneous etiology. This study aimed to investigate whether quantitative electroencephalography (qEEG) characteristics of delirium differ among etiology-based delirium subtypes or converge on common neurophysiological patterns. Methods: In this multicenter observational study, we analyzed qEEG data from 377 patients (173 delirious, 204 non-delirious) consecutively enrolled across three sites. Etiology-based delirium subtypes included post-stroke, medical and postoperative delirium diagnosed by staff physicians based on the Diagnostic and Statistical Manual of Mental Disorders-IV or 5 criteria. We compared peak frequency, relative power, and phase lag index (PLI) between delirious and non-delirious patients across different etiologies using standardized mean differences (SMDs) with 95% confidence intervals (CI). Results: Among spectral qEEG measures, there were no differences between subgroups. The peak frequency showed a consistent decrease between all delirium groups and non-delirious controls (SMD = -0.81, CI:-1.50 to −0.13), relative delta power increased (SMD = 1.44, CI:0.61 to 2.26), and relative beta power decreased (SMD = -1.72, CI:-2.46 to −0.97). Effect sizes differences in PLI between delirious and non-delirious controls were small and not consistent across subtypes. Conclusions: Our findings demonstrate consistent patterns in spectral qEEG characteristics across delirium subtypes, suggesting a common neurophysiological pathway of global EEG slowing in delirium regardless of etiology. By contrast, differences in PLI did not converge across subtypes. Multicenter studies should harmonize data collection to disentangle the shared and distinct neurophysiological changes associated with delirium of varying etiologies, in order to advance our understanding of potentially convergent mechanisms across subtypes.